Empirical rejection of mainstream economics' core postulates – on prices, firms' profits and markets structure - Joaquim Vergés-Jaime (Real-world economics review, 2020)
Mainstream economic theory relies largely on deductions from assumptions, rather than from inductive assertions based on a previous systematic gathering of observations on the basic elements of a market economy and its dynamics. This is the case for assumptions on: the general pattern of behaviour of firms' average costs in relation to the volume of units (returns to scale); prices determination (price theory); firms' size relative to market demand (market power); prevailing market structure regarding the competition/monopoly axis; people's economic behaviour (use of the "homo economicus" paradigm); socio-economic conditions (assumption of equality in income distribution, etc.); economically relevant information flows in technology, financial channels, etc. (perfect information); etc. All of this underpins the "standard model" core paradigm of the general equilibrium of competitive markets. The present paper is devoted to presenting the results of confronting two of these core assumptions with the extensive empirical evidence available regarding them. First, the assumption on "price determination - in relation to the respective average costs" - (price theory), and therefore on the relative relevance of firms' profits. Second, the one on "the prevailing market structure regarding the competition / monopoly" axis; or, in other words, on the overall pattern regarding firms' size relative to the respective market demand, for any product or service. As a result of this confrontation with observational evidence (hypothesis testing) it is argued here that these two "standard model" core assumptions cannot actually be sustained. As hypotheses on the economic world, they must be rejected. Therefore the economic theory built upon them is not a valid theory (from the perspective of the scientific method) to explain the workings of our market economies, to teach economics to newcomers at university class rooms, etc
Keywords: A11; B41; D21; D22; 330; Mainstream economics' assumptions; Standard economics' hypotheses' testing; Real world economics; Heterodox economics